The Importance of Being Earnest (1895) by Oscar Wilde: Conformity and Resistance in Victorian Society - Brigitte Bastiat (Cahiers Victoriens et Edouardiens)
The Importance of Being Earnest (1895) by Oscar Wilde is a popular play that is still widely performed in English-language theatres and also in many other languages. For example, the “Théâtre Antoine” in Paris produced it in October 2006 (on tour until March 2008) and a Versailles company performed it at “Le Lucernaire” in September and October 2008.When first performed, the play was considered as a light comedy and classified as entertainment for Victorian society. However, the writing of the play relies on a creativity and richness that combine different styles. Oscar Wilde was gay in a society stifled by social conventions and governed by very tough laws on homosexuality. Nevertheless, some critics have argued that the playwright dared include homosexual connotations in the text. However, I would argue that more generally, despite very little room for manœuvre, he managed brilliantly to challenge the social norms, sexual stereotypes and gender representations of his time while pleasing aristocratic London socialites.In this paper I will examine the way in which Wilde’s text challenged and conformed at the same time.